Collagen from Pangasius bocourti skin: extraction and antioxidant activities - Le, Trung Hieu; Le, Lam Son; Nguyen , Dang Giang Chau; Tran, Thanh Minh; Le, Thuy Trang; Nguyen , Hoang Luong Ngoc; Nguyen, Thi Nhu; Tran, Thi Van Thi (Hue University Journal of Science: Natural Science, 2023)
Fish skin discharged from the fish processing industry is an abundant source of raw material for collagen production. This work aims to optimise the experiment conditions for collagen extraction from Pangasius bocourti skin. The highest yield was obtained under the following optimal conditions: NaOH 0.1 M, citric acid 0.05 M for demineralisation and extraction, and 200 mL of 5% H2O2. The collagen was characterised from its IR spectra and SEM images, and the antioxidant activities of collagen were evaluated in vitro. The obtained collagen demonstrated appreciable total antioxidant activity, ABTS radical scavenging activity, and DPPH radical scavenging activity.